2023
DOI: 10.1126/sciadv.ade3557
|View full text |Cite
|
Sign up to set email alerts
|

CO electroreduction on single-atom copper

Abstract: Electroreduction of carbon dioxide (CO 2 ) or carbon monoxide (CO) toward C 2+ hydrocarbons such as ethylene, ethanol, acetate and propanol represents a promising approach toward carbon-negative electrosynthesis of chemicals. Fundamental understanding of the carbon─carbon (C-C) coupling mechanisms in these electrocatalytic processes is the key to the design and development of electrochemical systems at high energy and carbon conversion efficiencies. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 79 publications
(104 reference statements)
0
11
0
Order By: Relevance
“…The similar reconstruction of single-atom Cu under operating CO 2 reduction conditions was elucidated in the literature. The in situ formed sites include subnanometric Cu x ( x : 2, 3, or 4) clusters and nanoparticles with a size of ∼2–4 nm. , In contrast, many works demonstrated that carbon-supported single-atom Cu sites are electrochemically stable during the CO 2 reduction even at a negative potential of −1.6 V. The variance is probably due to the difference in local coordination of the single-atom Cu and supports’ structure/compositions of those reported catalysts, thus leading to different single-atom Cu–support interactions that mainly determine the electrochemical stability of the single-atom Cu center. In our case, single-atom Cu was converted into a Cu 3 /Cu 4 cluster at −0.8 to −1.6 V rather than larger nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The similar reconstruction of single-atom Cu under operating CO 2 reduction conditions was elucidated in the literature. The in situ formed sites include subnanometric Cu x ( x : 2, 3, or 4) clusters and nanoparticles with a size of ∼2–4 nm. , In contrast, many works demonstrated that carbon-supported single-atom Cu sites are electrochemically stable during the CO 2 reduction even at a negative potential of −1.6 V. The variance is probably due to the difference in local coordination of the single-atom Cu and supports’ structure/compositions of those reported catalysts, thus leading to different single-atom Cu–support interactions that mainly determine the electrochemical stability of the single-atom Cu center. In our case, single-atom Cu was converted into a Cu 3 /Cu 4 cluster at −0.8 to −1.6 V rather than larger nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Measured reaction orders of CO in the CORR on Cu are inconsistent with the hypothesis that the coupling of two CO ad species is the RDS. Reaction orders of CO in the CORR has been determined in the H-type, , the flow-type and the membrane electrode assembly (MEA) configurations, with highly consistent results (Table ). Formation rates of C 2+ products increase linearly at low p CO (≤0.4 atm), indicating a first order reaction.…”
Section: Mechanistic Implications Of Low Co Coveragesmentioning
confidence: 97%
“…In this scenario, directly collecting acetic acid in a neutral environment without other solutes during an efficient eCO 2 RR process in the MEA presents a significant challenge and has not been realized so far. Instead, electrochemical CO reduction reactions (eCORR) have proven to be more effective for efficient acetate production due to the lower acidity of CO compared to CO 2 . , However, compared with using inexpensive CO 2 as a feedstock, the adoption of the high-purity CO gas as a reactant can substantially escalate the cost of acetate production. In light of these challenges and considerations, it is imperative to advance the development of novel electrocatalytic systems that can enhance the performance of the eCO 2 RR to yield acetic acid.…”
Section: Introductionmentioning
confidence: 99%